The key role of DLX6 in nasopharyngeal carcinoma: metastasis, angiogenesis and tumor immune mechanism - Yang, Hanxuan; Zeng, Ximing; Chen, Xiaochuan; Cai, Sunqin; Li, Yi; Xu, Wenqian; Lai, Jinghua; Qiu, Sufang (Frontiers in Immunology, 2025)
BackgroundPrecise management of gene expression is vital for the correct growth and operational efficiency of cells. Early-stage nasopharyngeal carcinoma (NPC) often presents asymptomatically, leading to delayed diagnosis, limited treatment options, and increased risk of recurrence and metastasis. This study investigates the role of DLX6 in NPC pathogenesis to enhance early screening and treatment.Methods and materialsImmunohistochemistry and RNA sequencing were utilized to investigate the relationship between DLX6 expression in NPC tumor samples and clinical pathological factors. Clinical data from Fujian Cancer Hospital, along with sequencing analysis from the GEO databases, were used for bioinformatics analysis. NPC cell lines with DLX6 knockdown were established, and the impact of DLX6 on the biological traits of NPC cells was assessed through wound healing, transwell, colony formation, and EdU assays. The expression of EMT-related proteins and the PI3K-AKT pathways was examined using western blot analysis.ResultsImmunohistochemistry validated the association between DLX6 and NPC prognosis, whereas RNA sequencing illustrated its expression levels in tissues and cells. Functional assays such as wound healing, transwell, and colony formation revealed that DLX6 knockdown adversely affected NPC cell proliferation, invasion, and migration. Bioinformatics analysis revealed that DLX6 is involved in pathways related to cell cycle, DNA replication, and cancer progression. Immune infiltration analysis showed that DLX6 expression affects the immune landscape in NPC, correlating positively with DC and TH17 cells, and negatively with cytotoxic T cells and B cells. Low DLX6 expression was associated with higher levels of chemokines and better immunotherapy outcomes.ConclusionOur study indicates that DLX6 is a novel prognostic biomarker and potential therapeutic target for NPC, playing a critical role in metastasis, angiogenesis, and tumor immunity.